2021
DOI: 10.1021/acs.inorgchem.1c01734
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of a Family of Coumarin–Enamine Fluorescent Chemodosimeters for Ion Pairs

Abstract: A family of coumarin–enamine chemodosimeters is evaluated for their potential use as fluorescent molecular probes for multiple analytes [cadmium­(II), cobalt­(II), copper­(II), iron­(II), nickel­(II), lead­(II), and zinc­(II)], as their chloride and acetate salts. These fluorophores displayed excellent optical spectroscopic modulation when exposed to ion pairs with different Lewis acidic and basic properties in dimethyl sulfoxide (DMSO). The chemodosimeters were designed to undergo excited-state intramolecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…UV–vis absorption and fluorescence spectroscopies are the two most used methods in chemistry, biology, and materials sciences. Understanding the relationship between the fluorophore light absorption and fluorescence emission is important not only for a fundamental understanding of materials photophysical properties but also for reliable fluorescence analysis. While the origins of light absorption and fluorescence emission have become common knowledge for most fluorescent materials, the interplay among the sample light absorption and emission can be highly complicated in many practical fluorescence applications. Mechanistically, fluorophore light absorption must precede its fluorescence emission.…”
Section: Introductionmentioning
confidence: 99%
“…UV–vis absorption and fluorescence spectroscopies are the two most used methods in chemistry, biology, and materials sciences. Understanding the relationship between the fluorophore light absorption and fluorescence emission is important not only for a fundamental understanding of materials photophysical properties but also for reliable fluorescence analysis. While the origins of light absorption and fluorescence emission have become common knowledge for most fluorescent materials, the interplay among the sample light absorption and emission can be highly complicated in many practical fluorescence applications. Mechanistically, fluorophore light absorption must precede its fluorescence emission.…”
Section: Introductionmentioning
confidence: 99%
“…Coumarin, or 2H-chromen-2-one, is a natural bicyclic organic compound isolated from a variety of plants. Its derivatives have found broad applications such as fluorescent probes [1][2][3][4], food additives [5][6][7], in polymer chemistry [8][9][10][11], and so on. Numerous representatives have displayed variable bioactivity profiles [12][13][14][15][16][17][18], including anticancer [19][20][21][22][23][24], anti inflammatory [25][26][27], anti-tuberculosis [28,29], antimicrobial [30], and many others.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our group has shown that the anion can deprotonate the enol proton that is involved in the Resonance-Assisted Hydrogen Bonding interaction (RAHB) to form the bidentate binding motif (N^O − ), which drastically changed the optical response upon the addition of metal acetate salts in DMSO, by inhibiting the ESIPT mechanism and producing a CHEF signal upon the binding of metal ions. 10…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the acetate ion was initially used as the counter ion as we have previously shown that the metal acetate could deprotonate the OH group on the enol to form the chelating motif to coordinate with the metal ions. 10 The initial UV-Vis band is seen at 331 nm for QHC2 , assigned to the n–π* transition (the π–π* band is seen at 261 nm), with a calculated molar absorbance coefficient of 13 909 mol dm −3 cm −1 (Fig. S34†).…”
Section: Resultsmentioning
confidence: 99%